The Phenomenon of (Sustainable) Tourism Activities on Farms in Slovenia During the COVID-19 Pandemic - Žibert, Maja; Prevolšek, Boris (Studia Ecologiae et Bioethicae, 2022)
The outbreak of the COVID-19 pandemic is the reason why the development trends of the tourism industry are changing today. The purpose of this article is to address issues of future tourism industry development, linking it to elements of sustainable development trends. The article presents the main elements of the sustainable concept of rural and farm tourism. Using the method of compilation and description, we want to check, based on statistical data related to farm tourism activities in Slovenia (before and during the COVID-19 pandemic), whether it is possible to detect development trends in Slovenia, in the direction of sustainability that are linked to the concept of farm tourism. This study also aims to identify a number of measures that can improve sustainability at the farming tourism level in Slovenia, in a post-COVID phase. According to the findings of numerous comparisons and statistical analysis, it can be stated that the future development trends show a great need to develop the decarbonisation of the industry, digitalisation of industry, and the involvement of the local population in the provision of services. In the present global situation, we have reached a point where it will be necessary to focus on sustainable and digital forms of the industry, in order to further post-COVID development of the tourism industry.